2020
DOI: 10.1016/j.ijid.2020.06.078
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of the COVID-19 pandemic in the State of Kuwait

Abstract: Prompt understanding of the temporal and spatial patterns of the COVID-19 pandemic on a national level is a critical step for the timely allocation of surveillance resources. Therefore, this study explored the temporal and spatiotemporal dynamics of the COVID-19 pandemic in Kuwait using daily confirmed case data collected between the 23 February and 07 May 2020. Methods: The pandemic progression was quantified using the time-dependent reproductive number (R (t) ). The spatiotemporal scan statistic model was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 18 publications
3
58
0
Order By: Relevance
“…2B). This nding is surprising, especially as Alkhamis et al, inferred that signi cant spreading and cluster events in migrant workers communities were substantially more severe than residents-citizens due to their densely populated areas and poor living conditions [33]. A potential explanation for this, may be that migrant workers, tend to represent a much younger subset of the population in Kuwait [34].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2B). This nding is surprising, especially as Alkhamis et al, inferred that signi cant spreading and cluster events in migrant workers communities were substantially more severe than residents-citizens due to their densely populated areas and poor living conditions [33]. A potential explanation for this, may be that migrant workers, tend to represent a much younger subset of the population in Kuwait [34].…”
Section: Discussionmentioning
confidence: 97%
“…2C). We attributed this nding to the government's extensive intervention measures of testing and forced institutional quarantine of arriving travelers at the beginning of the epidemic in Kuwait [33]. Also, healthcare workers were more likely to develop symptoms despite having access to personal protective equipment during their duties (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As this point, Kuwait is dealing with two major sources of coronavirus, that is, Kuwaitis returning from affected countries such as the UK and USA, and migrant workers, most of whom are Indians, due to their cramped living conditions. Indeed, Alkhamis et al [17] pointed out the importance of maintaining migrant workers' health and living conditions in limiting the transmission of COVID-19 in Kuwait. A high contact rate among the population in Kuwait implies that the epidemic peak value is yet to be reached and that more strict intervention measures must be incorporated [25].…”
Section: Discussionmentioning
confidence: 99%
“…Newspapers report that their accommodation is too crowded, with perhaps 12 people living in a single room in a dilapidated building; they often lack soap, water, or hand sanitizer to clean their hands regularly, and are being neglected by their sponsors after losing their income. A study by Alkhamis et al [17] that used temporal and spatiotemporal epidemic dynamics of COVID-19 in Kuwait showed a distinct spreading and clustering events within and between migrant workers and citizen-residents communities. This study found out also that densely populated areas and poor living conditions of migrant workers resulted in the highest number of significant spreading and clustering events within their communities.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the first cases came from Iran, followed by cases from other countries including USA and UK, and the cases through community transmission involving migrant workers. Targeted intervention measures within migrant workers' communities in Kuwait substantially lowered the magnitude and the number of spreading and clustering events respectively [17].…”
Section: Discussionmentioning
confidence: 99%